Discovery of resonance-enhanced emission effect and its application in the design of fluorescent molecules. Issue 46 (22nd November 2022) - Liu, Xue; Ye, Wei; Lin, Wan; Cheng, Yinwei; Xu, Liyan; Li, Enmin; Zhang, Hefeng
Abstract : In addition to D–A effect and inter-molecular interaction, resonance enhanced emission effect promised a new perspective to understand the fluorescence mechanism and to develop dual-state emissive emitters with tunable emissions in full-color range. Abstract : Conjugated molecules are considered as resonance hybrids rather than a single molecular formula. Herein, we report a resonance enhanced emission (REE) effect discovered in hydrostyryl pyridinium (SP-OH ) derivatives. SP-OH derivatives with an electron-withdrawing group (EWG) on the phenyl ring exhibited dramatically bright and red-shifted fluorescence with large Stokes shifts and unexpected dual-state (solution and solid) emission (DSE) characteristics. Interestingly, EWGs such as nitrile and halide groups, especially the nitro group, showed a specific driving force for the REE effect and endow SP-OH families with full-color emissions ranging from blue to near infrared. The REE effect was attributed to the EWG-prompted deprotonation of the phenolic hydroxyl group and the consequent enhancement of the contributions of these highly emissive resonance contributors. SP-OH families derived from a simple skeleton showed advantages, including large varieties, low molecular weights, excellent emission performances, easy and low-cost preparation, and thus make the REE effect an efficient strategy for developing novel fluorescent molecules.